Cross-Coupling of Nonactivated Primary and Secondary Alkyl Halides with Aryl Grignard Reagents Catalyzed by Chiral Iron Pincer Complexes - Bauer, Gerald; Cheung, Chi Wai; Hu, Xile (Synthesis, 2015)
Iron(III) bisoxazolinylphenylamido (bopa) pincer complexes are efficient precatalysts for the cross-coupling of nonactivated primary and secondary alkyl halides with phenyl Grignard reagents. The reactions proceed at room temperature in moderate to excellent yields. A variety of functional groups can be tolerated. The enantioselectivity of the coupling of secondary alkyl halides is low.
Keywords: Kumada coupling; iron pincer complex; alkyl halide; aryl Grignard reagent; enantioselectivity